2013
DOI: 10.11118/actaun201361061575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bull, diluter and LDL-cholesterol concentration on spermatozoa resistance against cold shock

Abstract: The objectives of this study were to determine and evaluate the eff ect of bull, diluter and addition of LDL in diff erent concentration on the percentage rate of spermatozoa survival a er cold shock. In total, four bulls were collected during a period of eight weeks. A total of 8 samples of fresh semen with required quality were processed. Three extenders were used for dilution of each sample; AndroMed®, Bioxcell® and Triladyl®, each in standard and LDL enriched variants. In the case of AndroMed® and Bioxcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…In general we can say that considerable individual diff erences in sperm survivability between bulls were determined. This is in accordance with the work of Beran et al (2012 and2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general we can say that considerable individual diff erences in sperm survivability between bulls were determined. This is in accordance with the work of Beran et al (2012 and2013).…”
Section: Discussionsupporting
confidence: 92%
“…The potential fertility of sperm can be evaluated by several methods (Dhurvey et al, 2012). Cold shock test was evaluated in relation to LDL addition to diluters (Beran et al, 2013), but optimal LDL concentration increasing resistance of spermatozoa against cold shock was not suggested. Thus, the aim of this study was to determine the eff ect of the LDL addition to selected diluters on the rate of spermatozoa survival following cold shock and propose the optimal combination of the diluter and LDL concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The factors of bull's individuality or thawing method were detected as important in presented study as well as in many previous (Beran et al, 2013;Paldusová et al, 2016;Doležalová et al, 2016). Both these criteria should be therefore tested and proven in specified conditions to optimize methods of IDs processing.…”
Section: Discussionmentioning
confidence: 99%
“…However, resistance of sperm against cold shock has not been evaluated as well in relation to the addition of LDL. Moreover, the results of a previous study (Beran et al 2013b) have shown different results in relation to the concentration of LDL.…”
Section: Reproduction Bull Sperm Extender Ldl Cholesterol Sperm Smentioning
confidence: 95%